Polarization sensitive optical coherence tomography. - Lua, Wei Pei. (2012)
This paper reviews the principles and applications of optical coherence tomography (OCT), an optical imaging technique based on the correlation and interference between light backscattered from tissue and a reference light. It is an emerging, non-invasive imaging modality capable of producing micro-structural cross-sections of inhomogeneous samples (e.g. biological tissues).